Carbon isotope discrimination and water use efficiency in interspecific Prunus hybrids subjected to drought stress - Mininni, Alba N (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.